GamerGirls: as mulheres nos jogos digitais sob a visão feminina - Fonseca, Lívia Lenz (Universidade do Vale do Rio dos Sinos, 2013)
The essay have as objective study digital games and their repercussion on their target consumer public, but specifically on female game players. A formal approach of the games as technological mediatic artifacts as result of an extensive evolution in media devices of great importance. As well as in others medias, around those have formed an culture that establishes values and habits in contemporary society involving technology and communication.This work approaches how woman - public on a recently ascension into the gamer culture - are being represented and welcomed by players fans of those products. For this, I have made an theoretical approach about the relation between games and others recurrent medias on the market,followed by an analysis of the role of women in society and how she were represented in the media over the years. After that, there is an field research interviewing female game players and also some women who does not have the habit of playing games to find out their opinion regarding digital games and also about the female figure within these. These researches were made through online interviews and in person, besides one research in person where women reactions in front of games were observed. Using the collected data, I have made an conclusion on how the female figure is shown in these games and also how it is received and interpreted by contemporary women.
Keywords: Female; Culture; Digital games; Feminino; Cultura; Jogos digitais; ACCNPQ::Ciências Sociais Aplicadas::Comunicação